PENGEMBANGAN DAN PRODUKSI KONTEN DIGITAL SEBAGAI PRAKTIK KOMUNIKASI MEDIA DI TRIBUN SUMSEL - Rama Cahaya Arya; Merrieayu (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study is a case study based on an internship experience focusing on the development and production of digital content as a media communication practice at Tribun Sumsel over a 16-week period. The study employed a qualitative approach using observation, interviews, and literature review to understand the content management process and strategies for content development. During the internship, the researcher actively participated in managing the Jobhunter account, a flagship program providing job vacancy information, producing promotional content for business partners, and supporting activities such as podcast production, front office services, and event organization. The findings indicate that the success of digital content development and production depends on several key factors, including the quality of digital content through graphic design, video production, and engaging and relevant caption writing, consistent content publication, the regular and effective use of social media platforms, and collaboration with business partners to increase audience reach and engagement. This study contributes to the development of digital communication studies and online media practices, particularly in the field of digital media and content production.